Students’ Perceptions of Fairness, Human Rights, and Conflict in Papua: A Civic Education Study - Jevan Alzayn Edwin Saaluddin; Putu Ega Yudia Mastika (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2026)
This study examines how a contested national issue can be used as a civic education context for discussing fairness, human rights, and conflict. Using an exploratory qualitative descriptive design, the study combines purposive document analysis of public texts on Papua, justice, human rights, and peace with a school-based questionnaire administered to 18 respondents, most of whom were upper primary students. Four Likert-type items were used to capture perceptions of equal rights, mutual respect, fairness, and the relationship between injustice and conflict in Papua. The document data were analyzed through thematic grouping, while the questionnaire data were summarized using descriptive tabulation. The findings show that agreement and strong agreement dominated across all four items. Respondents strongly endorsed equal human rights, associated justice with fair treatment without discrimination, viewed mutual respect as relevant to conflict prevention, and tended to relate the Papua conflict to perceived injustice, although with greater neutrality on the Papua-specific item. The study contributes to civic education by showing that difficult national issues can be translated into age-appropriate, dialogic, and evidence-informed learning about rights, dignity, recognition, and peaceful coexistence.